2016
DOI: 10.1074/jbc.m116.719955
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Tm6sf2, a Gene Defective in Fatty Liver Disease, Impairs Lipidation but Not Secretion of Very Low Density Lipoproteins

Abstract: A missense mutation (E167K) in TM6SF2 (transmembrane 6 superfamily member 2), a polytopic protein of unknown function, is associated with the full spectrum of fatty liver disease. To investigate the role of TM6SF2 in hepatic triglyceride (TG) metabolism, we inactivated the gene in mice. Chronic inactivation of Tm6sf2 in mice is associated with hepatic steatosis, hypocholesterolemia, and transaminitis, thus recapitulating the phenotype observed in humans. No dietary challenge was required to elicit the phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
227
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(253 citation statements)
references
References 61 publications
(73 reference statements)
23
227
3
Order By: Relevance
“…A reduced capacity to secrete VLDL owing to genetic mutations/polymorphisms or pharmacologic interventions can contribute to hepatic steatosis. Notwithstanding, the marked reduction in VLDL‐TG secretion observed in L‐Them2 ‐/‐ mice did not cause excess lipid accumulation within the liver because FAs were oxidized rather than stored as TGs in lipid droplets in chow‐fed animals, whereas de novo FA synthesis appeared to be suppressed in the setting of overnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced capacity to secrete VLDL owing to genetic mutations/polymorphisms or pharmacologic interventions can contribute to hepatic steatosis. Notwithstanding, the marked reduction in VLDL‐TG secretion observed in L‐Them2 ‐/‐ mice did not cause excess lipid accumulation within the liver because FAs were oxidized rather than stored as TGs in lipid droplets in chow‐fed animals, whereas de novo FA synthesis appeared to be suppressed in the setting of overnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of rs738409 variant has also been the subject of extensive research in the last decade, which has led to the consensus that the G-NAFLD-risk allele is associated with a loss of function [39]. Collectively, the available evidence indicates that the variant participates in hepatocyte triacylglycerol remodeling [39-41]. On the other hand, we recently uncovered a novel role of rs738409 in global liver metabolism by performing high-throughput metabolic profiling of PNPLA3 siRNA-silencing and overexpression of wild type and mutant Ile148Met variants (isoleucine/methionine substitution at codon 148) in Huh/7 cells [42].…”
Section: Genetic Factors That Influence the Severity And Natural Histmentioning
confidence: 99%
“…Specifically, Kozlitina et al showed in vitro that murine hepatoma cells expressing the Lys167- TM6SF2 (E variant) protein have reduced expression levels compared with the wild-type [27], while Mahdessian demonstrated that TM6SF2 is localized in the endoplasmic reticulum and the ER-Golgi intermediate compartment of human liver cells [52]. Available experimental evidence indicates that, while TM6SF2 protein is required to mobilize neutral lipids for VLDL assembly [52], it is not required for secretion of apoB-containing lipoproteins [41]. …”
Section: Genetic Factors That Influence the Severity And Natural Histmentioning
confidence: 99%
“…Finally, a polymorphism in Transmembrane 6 superfamily member 2 (TM6SF2) has been identified by human genome-wide association studies to be associated with hepatic steatosis (147, 236). The polymorphism results in reduced VLDL secretion rates, because of impaired lipidation of nascent VLDL particles (236). Whether the control of VLDL secretion can be leveraged in the management of NAFLD remains unclear.…”
Section: Introductionmentioning
confidence: 99%